On the issue of organizational problems of state fire supervision in connection with the entering into force of the federal law on state control (supervision) and municipal control in the Russian Federation - Mordvinenko, Sergey E.; Pikush, Denis S.; Ershov, Aleksandr V. (Bezopasnostʹ tehnogennyh i prirodnyh sistem, 2021)
Introduction. Due to the updating of the legislative framework, the possibility of introducing the so-called "seamless" interdepartmental processes in the field of fire control and supervision is considered. The paper shows how insufficiently well-regulated actions of departments can become a factor that reduces the efficiency of work in this area and hinders its development. The importance of Federal Law No. 248-FZ of July 31, 2020 "On State Control (Supervision) and Municipal Control in the Russian Federation" was noted. At the same time, significant difficulties of its practical application are recognized. With references to the sources, it is shown that, addressing this problem, scientists demonstrate either a global, enlarged approach, or, conversely, study particular cases within the borders of one region, in relation to a specific group of objects of fire control and supervision. The relevance of the presented work lies in the fact that the authors offer an adequate solution to universal organizational problems. Problem Statement. The starting point in solving the tasks of this scientific work is the study of the text of Federal Law No. 248-FZ of July 31, 2020 "On State Control (Supervision) and Municipal Control in the Russian Federation". From the point of view of law enforcement practice, the authors had to evaluate innovations in the activities of the state fire supervision bodies of the Ministry of Emergency Situations of Russia, identify weaknesses if possible, make arguments in favor of organizational and, in particular, communication processes, identify ways to solve the problems. Theoretical Part. The new document is considered as an element of the evolutionary process of state policy in the field of monitoring the compliance with mandatory requirements, including in the field of fire safety. The main imbalances that can potentially reduce the efficiency of the relevant departments of the Ministry of Emergency Situations have been identified. Thus, the Regulation on Fire Safety provides for the collection, clarification and annual updating of accounting information about the objects of supervision. At the same time, only the names of procedures are given in the document. There is no scheme of actions that links the object of supervision with such features of the subject (official) as: knowledge, experience, workload, Internet skills, computer or digital technology, technical and organizational availability of information resources. According to the statistics, the urgent need for appropriate adequate solutions is dictated by objective reasons. Constructive and relatively easy-to-implement measures to overcome the identified imbalances are indicated. Conclusions. The results of scientific work presented in this article demonstrate the direction of further improvement of the professional activities of specialists in fire control and supervision, as well as the department as a whole. The results of the research suggest that at the present stage in Russia (and, in particular, in the Rostov region) the information base is sufficient to improve departmental processes. Two factors should be recognized as the main weaknesses of the system. This is clearly insufficient digitalization of departments and the lack of high-quality communications between departments of various levels and profiles.